Entrepreneurial passion and entrepreneurial intention: the role of social support and entrepreneurial self-efficacy - Neneh, Brownhilder Ngek (Studies in higher education (Dorchester-on-Thames), 2022)
This study extended the research on the relationship between entrepreneurial passion and entrepreneurial intention by developing a moderated mediation model. This study investigated whether entrepreneurial self-efficacy mediates this relationship. Also, this study examines whether the social support moderates this mediation model by conducting a moderated mediation analysis. Using a sample of 500 valid responses from university students, this study established that firstly, entrepreneurial passion positively affects entrepreneurial intention and entrepreneurial self-efficacy. Secondly, the indirect effect of entrepreneurial passion on entrepreneurial intention through entrepreneurial self-efficacy was significant and positive. Thirdly, social support had a positive and significant influence on entrepreneurial intention, while the indirect effect of entrepreneurial passion on entrepreneurial intention through entrepreneurial self-efficacy was moderated by social support. The study culminates with practical implications for scholars and policymakers in South Africa.